Epilepsy in Children with Cerebral Palsy at Liaquat National Hospital, Karachi - Mehtab Hussain, Nimrazahid Falak Abro, Nadeem Noor, Asma Noreen, Ghulam Muhammad Phull, Bushra Rafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:To document the frequency of Epilepsy among children with Cerebral Palsy at Liaquat National Hospital, Karachi. Duration: From 7th April 2018To6th October 2018 Methodology: Total 94patients who had developed mental delay and clinical examination showed the sign of upper motor neuron lesion like decrease/increase tone, loss of muscle mass, brisk reflexes, up going planter were included. Those who had history of two or more fits 24 hour apart without other cause were labeled as epilepsy. Results: There were 62.8 percent male and 37.2 percent female patients. Mean age was 4.99±2.77 years. Most common type was quadriplegia (54.3%). Mostly mother’s education was middle (31.9%) while mostly father’s education was primary (31.9%). Total 55.3% study subjects were found with epilepsy. Significant association of epilepsy was observed withresidence and family income. Conclusion: The study results showed high frequency (55.3%) of Epilepsy in cases with Cerebral Palsy.